Institutional foundations of disaster risk reduction policy: Exploring and elaborating on two different cases: Argentina and Sweden. Issue 2 (1st April 2019) - De Majo, Veronica; Olsson, Jan
Abstract : Purpose: The purpose of this paper is to explore and elaborate on how institutional conditions work to the advantage and disadvantage of disaster risk reduction (DRR) policies on different levels in two countries. Design/methodology/approach: A qualitative case study design is used to study empirically two countries with very different traditions when it comes to political-administrative institutions: Argentina and Sweden. Findings: As expected, the institutional foundations of DRR policy in Sweden are shown to be more consistent and stable than in Argentina. However, this difference is of less importance when considering the crucial role of local practices. National institutional foundations can function as support – but is not a necessary condition – for building disaster preparedness on the ground. The authors argue that national governments cannot do without institutionalized praxis-based preparedness, which is vital for both effective emergency management and learning. Originality/value: This paper contributes to the disaster research debate by elaborating on institutional arrangements that can facilitate or hinder DRR strategies in a multi-level context. The main argument is that institutional practices on the ground are important to compensate for insufficient national institutions, either because they are weak or too distant from practical DRR. The authors also elaborate on how institutional practices can function as a source for learning and for building legitimate practical authority from the bottom up.